Design of an integrated tunable differential negative resistance in UMC 0.18 μm. (February 2016) - Richelli, A.; Grassi, M.; Redouté, J.-M.
Abstract: This paper presents a CMOS floating tunable differential resistance, which has the property of being positive with respect to common-mode signals while being negative for differential signals. The designed circuit is simulated in UMC 180 nm CMOS process: simulations show that the negative differential resistance can be varied in a broad range, from 23.5 kΩ to 3.8 MΩ.